Herbicida seletivo a partir de extratos de Piper Nigrum L. - Nogueira, Enes Follador (2019)
The increase in world demand for food leads to a higher consumption of agrochemicals. In this scenario, Brazil emerges as one of the world's leading consumers of pesticides, especially herbicides (about 45% of total consumption), which are highly harmful to the environment and to human health. In this context, researches have investigated natural products with a more sustainable performance. In this sense, allelopathy is shown as a viable alternative. The objective of this research was to evaluate the allelopathic activity of Piper nigrum L. and piperine alkaloid seeds and leaves extracts on the germination and initial growth of Lactuca sativa L. and Panicum maximum Jacq. For this, the IVG parameters were evaluated; G; TMG; IA; the activity of antioxidant enzymes SOD, CAT and POX; soluble sugars and starch contents and the concentrations of chlorophyll a, chlorophyll b and carotenoids in seedlings of Panicum maximum Jacq. (guinea grass), submitted to extracts containing piperine, aiming to understand the allelopathic effect of this alkaloid on the weed. Seed extracts of Piper nigrum L., in particular the EAQS800 extract, inhibited germination and initial growth of guinea grass without, however, significantly affecting the germination and initial growth of lettuce. The most abundant allelochemical found in the phytochemical prospecting of the pepper seeds extracts of the kingdom was the piperine alkaloid and, possibly, is the main component responsible for the allelopathic effect of these extracts on the weed. There was a reduction in the concentrations of glucose, fructose and sucrose in the plants exposed to EAQS800, however, a proportional increase of the starch concentration was also observed when compared to the control. There was an increase in the antioxidant activity of the POX enzyme accompanied by a reduction in the activity of the SOD and CAT enzymes, which probably promoted a lignification of the cell walls inhibiting the growth of the grass seedlings submitted to the extracts.